Comparison of scores for predictability of corticosteroid failure in patients with acute severe ulcerative colitis - Knežević Milica A.; Janjić Nebojša M.; Lečić Vuk B.; Todorović Nemanja B.; Damjanov Dimitrije D. (Hospital Pharmacology)
Introduction: Methylprednisolone and hydrocortisone are the first-line drugs in the treatment of acute severe ulcerative colitis (ASUC). The Oxford index and the Lindgren score are two of several prognostic systems for the early assessment of corticosteroid (CS) failure. Aim: The aim of the study was to determine the clinical course and treatment outcome of patients with ASUC and the difference between the Oxford criteria and the Lindgren score in identifying patients with CS-refractory ASUC. Material and Methods: A retrospective clinical trial included 30 patients with ASUC. They were divided into a group with complete response to intravenous CS therapy and one without. Demographic and clinical parameters associated with CS failure were analyzed statistically. In order to test the hypotheses, a chi-square test was applied. Results: After the third day of therapy, 70% of patients did not have a complete response to CS therapy based on the Oxford index value. These patients had a 91% higher risk of receiving rescue therapy (infliximab), while this risk is 2.67 times higher in patients with a Lindgren score >8 (it was recorded in 53.3% of patients). Statistically significantly lower values of the Lindgren score were found in the group with a complete response to CS therapy. A third of the patients from the examined group received rescue therapy, no patient was surgically treated and there were no cases of fatal outcome. In relation to rescue therapy, the Lindgren score >8 showed a higher positive predictive value (62.5% vs 47.6%) and higher specificity (70% vs 45%) than the Oxford index, while the negative predictive value and sensitivity of both scores amounted to 100%. Conclusion: Pharmacotherapy with intravenous CS was effective in most acute severe ulcerative colitis patients, but in a certain number of patients it was necessary to include rescue therapy. The Lindgren scoring system is specific and has a higher predictive value in identifying CS-refractory patients compared to the Oxford index values.